URGENSI KOMPETENSI GURU DALAM PEMBELAJARAN ONLINE DI MASA PANDEMI COVID 19 - Imam Subhi (PASCASARJANA UNISNU, 2020)
AbstractIn online learning the teacher becomes a strategic position that can support the effectiveness of learning, therefore teachers must have reliable competence in order to be able to be active and innovative in managing distance learning. Therefore this article will discuss competencies such as what should be owned by a teacher so that online learning can run well even though it will not be the same as the quality of learning face to face.Keywords. Teacher competence, online learning